What's in a word - Hata, Sandy (Te Kaharoa, 2012)
Language is the cornerstone of communication and can be conveyed in many forms.  One such form is composition or song.  There are many indigenous compositions that provide a backdrop reflecting the landscape, events and relationships that were integral to and impacted on the life of the composer and their communities.As a research subject, compositions from the early nineteenth century provide a template with which to analyse the language used and its relevance in today’s environment.  Written languages change with the introduction of new technologies and environments. Compositions such as laments have stayed intact as part of an oral tradition.  This research aims to examine whether the written history and poetic prose of the words within compositions has also stayed intact and been maintained. Specific words will be analysed in relation to their usage within both a traditional and modern context.